Comparison of Image Quality of Shoulder CT Arthrography Conducted Using 120 kVp and 140 kVp Protocols - Ahn, Se Jin (Korean J Radiol, 2014)
OBJECTIVE: To compare the image quality of shoulder CT arthrography performed using 120 kVp and 140 kVp protocols. MATERIALS AND METHODS: Fifty-four CT examinations were prospectively included. CT scans were performed on each patient at 120 kVp and 140 kVp; other scanning parameters were kept constant. Image qualities were qualitatively and quantitatively compared with respect to noise, contrast, and diagnostic acceptability. Diagnostic acceptabilities were graded using a one to five scale as follows: 1, suboptimal; 2, below average; 3, acceptable; 4, above average; and 5, superior. Radiation doses were also compared. RESULTS: Contrast was better at 120 kVp, but noise was greater. No significant differences were observed between the 120 kVp and 140 kVp protocols in terms of diagnostic acceptability, signal-to-noise ratio, or contrast-to-noise ratio. Lowering tube voltage from 140 kVp to 120 kVp reduced the radiation dose by 33%. CONCLUSION: The use of 120 kVp during shoulder CT arthrography reduces radiation dose versus 140 kVp without significant loss of image quality.